Rationally designed catalyst layers toward "immortal" growth of carbon nanotube forests: Fe-ion implanted substrates. (November 2019) - Lee, Cheol-Hun; Lee, Jaegeun; Park, Junbeom; Lee, Eunyoung; Kim, Seung Min; Lee, Kun-Hong
Abstract: To increase the length and coherence of carbon nanotube (CNT) forests that are grown by chemical vapor deposition, we implant Fe ions into an Al2 O3 supporting layer to weaken the gradient of Fe concentration when Fe catalyst layer is deposited on it. The weakened gradient slows loss of Fe catalyst nanoparticles (NPs) by sub-surface diffusion into the Al2 O3 layer. Therefore, Fe catalyst NPs were well maintained on the Fe-implanted substrates after growth for up to 660 min, whereas significant loss of Fe NPs occurred due to sub-surface diffusion into the Al2 O3 supporting layer on the non-implanted substrates. The lifetime of the catalyst was extended to 660 min (Fe-implanted substrate) from 540 min (non-implanted substrate), and the lengths of CNTs in the forest were increased to 20.3 ± 1.0 mm (Fe-implanted substrate, maximum 21.5 mm) from 15.8 ± 1.9 mm (non-implanted substrate). This study clearly demonstrates that sub-surface diffusion of Fe catalyst NPs into the supporting layer is the mechanism that limits CNT forest growth and may provide insights into development of methods to design an "immortal" catalyst to grow CNT forests. Graphical abstract: Image 1